Some Problems in the Estimation of Personal Savings and Investment - Saunders, C. T. (Review of Economic Studies, 1954)
Some Problems in the Estimation of Personal Savings and Investment Get access C. T. Saunders C. T. Saunders London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 2, 1954, Pages 109–128, https://doi.org/10.2307/2296286 Published: 01 January 1954